CRISPR-Cas9 therapeutics in cancer: promising strategies and present challenges - Yi, Lang; Li, Jinming (Biochimica et Biophysica Acta (BBA) - Reviews on Cancer, 2016)
Cancer is characterized by multiple genetic and epigenetic alterations that drive malignant cell proliferation and confer chemoresistance. The ability to correct or ablate such mutations holds immense promise for combating cancer. Recently, because of its high efficiency and accuracy, the CRISPR-Cas9 genome editing technique has been widely used in cancer therapeutic explorations. Several studies used CRISPR-Cas9 to directly target cancer cell genomic DNA in cellular and animal cancer models which have shown therapeutic potential in expanding our anticancer protocols. Moreover, CRISPR-Cas9 can also be employed to fight oncogenic infections, explore anticancer drugs, and engineer immune cells and oncolytic viruses for cancer immunotherapeutic applications. Here, we summarize these preclinical CRISPR-Cas9-based therapeutic strategies against cancer, and discuss the challenges and improvements in translating therapeutic CRISPR-Cas9 into clinical use, which will facilitate better application of this technique in cancer research. Further, we propose potential directions of the CRISPR-Cas9 system in cancer therapy. •The CRISPR-Cas9 system has been used in cancer therapeutic studies.•The potential of CRISPR-Cas9-based therapy strategies in cancer are discussed.•Technical challenges and improvements in clinically applying CRISPR-Cas9 are outlined.•Suggestions for further research of the CRISPR-Cas9 in cancer treatment are proposed.